The influence of X-ray irradiation on dynamical and structural characteristics of strained NaCl crystals - Petchenko, O.M.; Petchenko, G.О.; Boiko, S.М.; Bezugly, A.V. (Вопросы атомной науки и техники, 2020)
The influence of a preliminary deformation ε = 1,3% and X-ray irradiation to exposure doses 0…600 R on the frequency spectra of the dislocation ultrasonic absorption Δd(f) in NaCl crystals in the frequency interval 37,5…232,5 MHz and at room temperature has been studied using the pulsed technique. From the frequency curves, taken from crystals with different doses of radiation, the dependencies of the viscosity coefficient B and the average effective length of the dislocation segment L from the dose of irradiation has been determined. The coefficient of dynamic viscosity B was found to be independent of the irradiation dose.